2012
DOI: 10.2147/copd.s33714
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-binding lectin deficiency and acute exacerbations of chronic obstructive pulmonary disease

Abstract: Background:Mannose-binding lectin is a collectin involved in host defense against infection. Whether mannose-binding lectin deficiency is associated with acute exacerbations of chronic obstructive pulmonary disease is debated.Methods:Participants in a study designed to determine if azithromycin taken daily for one year decreased acute exacerbations had serum mannose-binding lectin concentrations measured at the time of enrollment.Results:Samples were obtained from 1037 subjects (91%) in the trial. The prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 49 publications
2
5
0
1
Order By: Relevance
“…A previous study, using same methodology, reported that the mean serum MBL level is 686.7±339.2 ng/mL in adult asthmatic patients, which is significantly higher than in healthy controls (358.3±180.4 ng/mL) 23. Moreover, the MBL level of COPD patients is reported to be 918 ng/mL, which measured by the same method 32. Elevated MBL levels are also noted in childhood asthmatic patients with a positive correlation with peripheral blood eosinophils 27.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…A previous study, using same methodology, reported that the mean serum MBL level is 686.7±339.2 ng/mL in adult asthmatic patients, which is significantly higher than in healthy controls (358.3±180.4 ng/mL) 23. Moreover, the MBL level of COPD patients is reported to be 918 ng/mL, which measured by the same method 32. Elevated MBL levels are also noted in childhood asthmatic patients with a positive correlation with peripheral blood eosinophils 27.…”
Section: Discussionmentioning
confidence: 71%
“…Samples were diluted at a ratio of 1:4,000 for the assay and measured in duplicate as previously reported 2332. A high serum MBL level was defined as one which was greater than the mean serum MBL level (675.5 ng/mL).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies on the impact of MBL deficiency in COPD are inconsistent; none have enrolled >300 patients without preselection for a subset of patients with COPD, that is, frequent exacerbators, 23 or had sufficient follow-up time to evaluate exacerbation frequency, whereas we analysed the electronic medical record data from 1796 patients with COPD with an average follow-up of 5.4 years. In the present study, MBL deficiency status was not found to have an effect on decline in FEV 1 , mortality or hospital admissions for cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that chronic inflammatory and immune responses play key roles in the development and progression of COPD [60,61] . In this respect, most of the potential biomarkers included in our list are proteins involved in inflammation or the immune response such as CRP, IL-6, beta defensin 2, among many others [25][26][27]29,36,37,54,[62][63][64][65][66][67][68][69][70][71][72][73][74] . One of the main causes leading to COPD is chronic smoking which exposes the respiratory tract to reactive oxygen species, resulting in oxidative stress and injury (which in the last instance leads also to inflammation) [59,75] .…”
Section: Copd Protein Biomarkersmentioning
confidence: 99%